Challenges of Successful Implementation of Artificial Intelligence in Logistics Project Management at Saudi Telecom Company - Al-Subaie, Norah Abdullah (Journal of Economic, Administrative and Legal Sciences, 2025)
The emergence of artificial intelligence (AI) technology has the capability to drastically change logistics and supply chain management across various business and industrial sectors. Logistic project management, a crucial sector in the supply chain management of companies, is regarded as a domain where AI will play a key role in enhancing efficiency, precision, and the speed of service delivery. Saudi Arabia’s Vision 2030 aims to improve connectivity with other nations both regionally and globally by refining logistics services, streamlining trade exchanges, and incorporating digital technology into these processes. The aim of this study is to identify the challenges faced when implementing AI technologies in logistics project management at Saudi Telecom Company (STC). This research employs a qualitative approach that features a literature review on the topic. The findings revealed several challenges impeding the global implementation of AI in logistics project management, which can be classified into organizational, technological, economic, data, environmental, social, and ethical issues. In the Saudi context, within the STC, four key challenges of implementing AI in logistics project management were recognized: data privacy and security, hardware infrastructure needs, insufficient employee skills and adaptability, and social acceptance. Based on the findings of this study, it can be concluded that implementing AI technology in logistics project management, when executed correctly, could reveal significant opportunities at the STC. Further experimental studies are suggested to gain a better understanding of the challenges that restrict the application of AI technology in logistics project management.